A comparative analysis between price‐penalty factor method and fractional programming method for combined economic emission dispatch problem using novel hybrid CSA‐JAYA algorithm. Issue 4 (14th April 2021) - Dey, Bishwajit; Basak, Sourav; Bhattacharyya, Biplab
Abstract: Economic dispatch of power is no more a sole concern for utilities. Instead, the utilities focus on reducing toxic gases emitted to the atmosphere due to the maximum utilisation of conventional fossil‐fuelled generators to meet the surging demand for electricity. This can be carried out by involving renewable energy sources (RES) to generate clean power compensating the depletion in the availability of fossil fuels. This article performs combined economic emission disfpatch (CEED) on four dynamic systems with and without the involvement of RES. Two methods for solving CEED, namely the price‐penalty factor (ppf) method and the fractional programming (FP) method, are used to perform CEED for all the four test systems, and a comparative analysis between them is made based on the least emission of harmful and toxic gases into the atmosphere. A novel hybrid (CSA‐JAYA) algorithm is used as the optimisation tool for the study. Numerical results manifest that the FP method of solving CEED is economic and emits less toxic gases to the atmosphere than the ppf method. The proposed hybrid CSA‐JAYA outperformed a long list of algorithms from recent literature in consistently providing better and superior quality solutions.